Cytopathologic characteristics and differential diagnostic considerations of osteolytic myxopapillary ependymoma. Issue 9 (1st August 2013) - Hayashi, Toshitetsu; Haba, Reiji; Kushida, Yoshio; Kadota, Kyuichi; Katsuki, Naomi; Bando, Kenji; Shibuya, Shinsuke; Matsunaga, Toru
<x xml:space="preserve">Abstract</x> Myxopapillary ependymoma (MPE) is a rare variant of conventional ependymoma found predominantly in the sacrococcygeal region in young adults and characterized by its distinct epithelial and stromal components (WHO grade I designation). MPE with extensive osteolysis is extremely uncommon and only up to 40 cases have been documented. A case is presented here in which imprint smears of a sacral tumor in an 18‐year‐old man revealed complex papillary structures, small loose clusters, or cord‐like structures of bland tumor cells embedded in a myxoid or mucinous background. The tumor cells possessed uniformly round nuclei with a smooth nuclear outline, fine granular chromatin, and small nucleoli. Slender cytoplasmic fibrillary processes and occasional intracytoplasmic vacuoles were observed. A cytologic diagnosis of a MPE was suggested and histochemical and immunohistochemical studies were conducted on formalin‐fixed, paraffin‐embedded material. Immunohistochemically, the tumor cells showed diffuse and strong membranous and cytoplasmic staining for cytokeratin AE1/AE3, glial fibrillary protein, and S‐100 protein, but negative for epithelial membrane antigen, pan‐neuroendocrine markers (i.e., NSE, chromogranin A, synaptophysin), or brachyury. The proliferative index with MIB‐1 was around 10%. The diagnosis of osteolytic MPE was confirmed based on cytopathologic, histopathological, immunohistochemical results, radiologic findings, and the location of the tumor. We demonstrated here the cytopathological features of osteolytic MPE with emphasis on differential diagnostic considerations. Diagn. Cytopathol. 2014;42:778–783. © 2013 Wiley Periodicals, Inc.